Value-added taxation in Europe - Schiff, Eric (Washington: American Enterprise Institute for Public Policy Research, 1973)
The subject treated systematically in this study is the effect of VAT on prices
Includes bibliographical references.
obn 22/01/2019
Loans
Keywords: Value-added tax